Economic policy uncertainty in merges and acquisitions: real options analysis - Costa, Gilmarques Agapito (2023)
The Real Options Theory (ROT) framework in relation to the Economic Policy Uncertainty Index (EPU) requires further empirical reinforcement, especially within the context of investment projects in mergers and acquisitions (M&A). There are still gaps in this theoretical domain that need to be explored. To contribute to the discussion, this study aims to investigate the impact of EPU on the valuation process of M&A transactions using the Discounted Cash Flow (DCF) method expanded by Real Options (ROV). To operationalize the evaluation, a model was proposed that involves standardizing the EPU variable and reorganizing it through Principal Components Analysis (PCA). This approach resulted in the creation of four non-discretionary scenarios for testing estimation. Additionally, four discretionary scenarios were generated through 10,000 simulations of possible paths for the EPU variable using the Geometric Brownian Motion (GBM) process. In the test environment, the results indicated that the non-discretionary approach, which solely relied on the characteristics of the PCA-transformed samples and estimation through DCF expanded by ROV, proved suitable for estimating values while considering the EPU volatility. The developed model was applied to the acquisition of Latinex by M. Dias Branco, and the obtained values closely aligned with those disclosed by the company in its financial statements. Furthermore, these values were found to vary based on the level of EPU volatility. The sensitivity tests conducted confirmed the appropriateness of the proposed non-discretionary model for incorporating the EPU volatility. It was concluded that an increase in the EPU volatility level can lead to higher project values, increased option values, and greater associated risks. These findings contribute to the understanding of the effects of EPU volatility on M&A valuations and emphasize the importance of considering economic policy uncertainty in investment decision-making processes.